Does intraoperative contamination during primary knee arthroplasty affect patient-reported outcomes for patients who are uninfected 1 year after surgery? A prospective cohort study of 714 patients - Justesen, Tobias; Olsen, Jakob B; Hesselvig, Anne B; Petersen , Anne Mørup-; Odgaard, Anders (Acta Orthopaedica, 2020)
Background and purpose — It is well recognized that some knee arthroplasty (KA) patients present with pro- longed postoperative inflammation and some develop persis- tent pain. It can reasonably be speculated that some of these problems develop because of low-grade infections with low virulence bacteria caused by intraoperative contamination. This prospective study was performed to investigate whether intraoperative contamination results in lower patient-reported outcomes (PRO) for patients who were clinically uninfected in the first year after surgery. Patients and methods — We combined data from 2 major prospective studies on patients undergoing primary KA at 2 Danish hospitals between September 2016 and January 2018. Pre- and postoperative (1.5, 3, 6, and 12 months) PROs and intraoperative microbiological cultures were obtained on a total of 714 patients who were included in the study. Based on the microbiological cultures, the patients were divided into 2 groups, contaminated and non-contaminated, and differences in PROs between the 2 groups were analyzed. Results — 84 of 714 (12%) patients were intraoperatively contaminated; none of the 714 patients developed clinical infection. The preoperative Oxford Knee Score was 24 and 23 for contaminated and non-contaminated patients, respectively, improving to 40 and 39 at 1 year (p = 0.8). 1-year AUC for Oxford Knee Score and absolute improvement at each postoperative time point for Forgotten Joint Score and EQ-5D-5L also were similar between contaminated and non- contaminated patients. Interpretation — Patient-reported outcomes from 714 patients do not indicate that intraoperative contamination affects the knee-specific or general health-related quality of life in primary KA patients who are clinically uninfected 1 year after surgery.